Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dan NHT Ditinjau dari Kecerdasan Interpersonal Siswa pada Pokok Bahasan Bangun Ruang Sisi Datar - Kurniawati, Kiki Riska Ayu; Budiyono; Saputro, Dewi Retno Sari (Mathematics Education Journal, 2017)
The aims ofthis research were to find out the different effect of each categories of learning model, students interpersonal intelligence and their interaction towards students mathematics learning achievement on the subject of plane geometry.The research was quasi experimental with 3×3 factorial design. The hypothesis test used unbalanced two ways analysis of variance at the significance level of 0,05. Based on hypothesis test, it can be concluded that: (1) the cooperative learning model of Jigsaw type gives a better mathematics achievement than cooperative learning model of NHT type and direct learning model, and the cooperative learning model of NHT type gives a better mathematics achievement than direct learning model; (2) students with the high interpersonal intelligence had the same achievement as students with the medium interpersonal intelligence, students with the high interpersonal intelligence had better achievement than students with the low interpersonal intelligence, and the students with the medium interpersonal intelligence had the same achievement as students with the low interpersonal intelligence; (3) on the cooperative learning model of Jigsaw type, NHT type and direct learning model, students with the high interpersonal intelligence had the same achievement as students with the medium interpersonal intelligence, students with the high interpersonal intelligence had better achievement than students with the low interpersonal intelligence and the students with the medium interpersonal intelligence had the same achievement as students with the low interpersonal intelligence; and (4) on students interpersonal intelligence high, medium and low, the cooperative learning model of Jigsaw type gives a better mathematics achievement than cooperative learning model of NHT type and direct learning model, and the cooperative learning model of NHT type gives a better mathematics achievement than direct learning model.